Match-play activity analysis in amateur female rugby union players using global positioning system - Westbrook, H. R. (Journal of Australian Strength and Conditioning, 2018)
The aim of this pilot study was to provide an objective description of the locomotive activities undergone during a club-level female rugby union match. Six players were analyzed using global positioning system tracking technology. Total distance covered by the players during the match was 4,284 ± 348 m. The backs covered 9% more distance than the forwards (4,487 ± 347 m vs. 4,081 ± 243 m, respectively). The intensity distribution of the distance covered in each locomotion zone was: 45.9% (1,965 ± 199 m) standing or walking, 32.3% (1,385 ± 190 m) jogging, 8.9% in low speed running (382 ± 96 m), 8.9% in moderate speed running (381 ± 145 m), 2.1% in high speed running (88 ± 59 m), and 2% sprinting (84 ± 74 m). There were obvious differences in the distance covered by forwards and backs in certain speed zones. The second (700 ± 87 m) & sixth (703 ± 100 m) 10-min periods saw the athletes cover the most distance. The average number of sprints, average maximum distance of sprinting, and average sprint distance during the game were 2.3 ± 2.4 sprints, 24.3 ± 8.6 m, and 11.8 ± 5.1 m, respectively. There were substantial differences between forwards and backs. Backs covered greater total distance, distance in the faster speed zones, and a higher number of sprints. These findings, along with previous research, offer vital information in designing better training strategies for female rugby union athletes. These include increasing the aerobic capacity, the total number of maximal accelerations (5 - 20 accelerations), and repeated (3-6 efforts) and single sprint efforts over varying distances (5m-40m).